Tracking of peptide-specific CD4+ T-cell responses after an acute resolving viral infection: a study of parvovirus B19. - Kasprowicz, V; Isa, A; Tolfvenstam, T; Jeffery, K; Bowness, P; Klenerman, P (2006)
The evolution of peptide-specific CD4(+) T-cell responses to acute viral infections of humans is poorly understood. We analyzed the response to parvovirus B19 (B19), a ubiquitous and clinically significant pathogen with a compact and conserved genome. The magnitude and breadth of the CD4(+) T-cell response to the two B19 capsid proteins were investigated using a set of overlapping peptides and gamma interferon-specific enzyme-linked immunospot assays of peripheral blood mononuclear cells (PBMCs) from a cohort of acutely infected individuals who presented with acute arthropathy. These were compared to those for a cohort of B19-specific immunoglobulin M-negative (IgM(-)), IgG(+) remotely infected individuals. Both cohorts of individuals were found to make broad CD4(+) responses. However, while the responses following acute infection were detectable ex vivo, responses in remotely infected individuals were only detected after culture. One epitope (LASEESAFYVLEHSSFQLLG) was consistently targeted by both acutely (10/12) and remotely (6/7) infected individuals. This epitope was DRB1*1501 restricted, and a major histocompatibility complex peptide tetramer stained PBMCs from acutely infected individuals in the range of 0.003 to 0.042% of CD4(+) T cells. Tetramer-positive populations were initially CD62L(lo); unlike the case for B19-specific CD8(+) T-cell responses, however, CD62L was reexpressed at later times, as responses remained stable or declined slowly. This first identification of B19 CD4(+) T-cell epitopes, including a key immunodominant peptide, provides the tools to investigate the breadth, frequency, and functions of cellular responses to this virus in a range of specific clinical settings and gives an important reference point for analysis of peptide-specific CD4(+) T cells during acute and persistent virus infections of humans.